2018
DOI: 10.1186/s12931-018-0959-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on the lower respiratory tract microbiome in mice

Abstract: BackgroundRecent studies break with traditional opinion that the lower respiratory tract is sterile, and increasingly focus on the lung microbiome and disease. Smoking, as an important etiology of inflammatory lung disease, was considered as a factor influencing lung microbiome variations in our study, and we aimed to study the effect of smoking on inflammation and microbial diversity and community.MethodsForty male mice were selected and randomly divided into a smoking and a non-smoking group. Mice in the smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 59 publications
2
31
0
2
Order By: Relevance
“…In recent years, it has been shown that the lungs of healthy smokers contain a bacterial microbiome that is quantitatively and qualitatively diverse from that of the oral cavity and extra-thoracic airways [43]. However, the role of microbial diversity remains unclear, since in contrast with Zhang et al [42], human LMt diversity is often lower in subjects with poor lung function, and it is most commonly associated with dominance by Pseudomonas spp. The fact that some smokers, with spirometric evidence of lung disease, had a less different LMt compared with smokers, with normal lung function, and indicates that LMt changes can be an earlier sign of respiratory disease [43].…”
Section: Lung Microbiota and Smokementioning
confidence: 97%
See 2 more Smart Citations
“…In recent years, it has been shown that the lungs of healthy smokers contain a bacterial microbiome that is quantitatively and qualitatively diverse from that of the oral cavity and extra-thoracic airways [43]. However, the role of microbial diversity remains unclear, since in contrast with Zhang et al [42], human LMt diversity is often lower in subjects with poor lung function, and it is most commonly associated with dominance by Pseudomonas spp. The fact that some smokers, with spirometric evidence of lung disease, had a less different LMt compared with smokers, with normal lung function, and indicates that LMt changes can be an earlier sign of respiratory disease [43].…”
Section: Lung Microbiota and Smokementioning
confidence: 97%
“…These substances contact the respiratory mucosa and are associated with chronic inflammation in smokers. Recently, Zhang et al [42] studied that 40 mice exposed to tobacco smoke and observed that microbial diversity was higher in the smoking group, suggesting that smoke exposure increases the risk of bacterial infection, thereby increasing microbial diversity. The authors concluded that smoking influences microbial diversity and communities of the lower respiratory tract, suggesting that future studies on smoke-induced inflammation should also consider the LMt variation [42].…”
Section: Lung Microbiota and Smokementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Munck et al reported the lack of important changes in bacterial diversity after smoking cessation [83], indicating that smoking does not have a key role in determining modifications in lung commensal composition. On the other hand, studies performed in humans [74] and mice [84] suggested that smoke exposure can alter bacterial composition in the lower respiratory tract, probably by impairing local immune cell activity. Since chemical compounds present in the tobacco smoke may affect lung immune cells function [85,86], smoking may determine a disequilibrium in the microbiota-immune cell cross talk, leading to dysbiosis, chronic infection and, eventually, lung cancer.…”
Section: Lung Microbiota Smoke and Cancermentioning
confidence: 99%
“…Overall, the dominant microorganisms at the phylum level in healthy pig lungs were Proteobacteria , Firmicutes , and Bacteroidetes , which are similar to the lung microorganisms present in humans [ 12 , 34 ], mice [ 35 , 36 ], and cattle [ 21 , 37 ]. This finding indicates that the composition of lung microorganisms in healthy individuals of different species is comparable.…”
Section: Discussionmentioning
confidence: 91%